A Discovery of a Hidden Legacy in the Bektashi Tradition: An Examination of Bedri Noyan Dedebaba’s Unpublished Poems and Their Sufi Depth - Erdem, Cem (Journal of Alevism-Bektashism Studies, 2024)
This study aims to analyze 23 previously unpublished poems by Bedri Noyan Dedebaba, focusing on their content, language, and stylistic features. Bedri Noyan Dedebaba, as the 36th leader (mürşid) of the Babagan branch within the Bektashi tradition, holds a significant place and has had a wide-reaching influence through his mystical poetry. In this study, Dedebaba’s understanding of Sufism is observed to center around themes such as divine love, the struggle with the self (nafs), moral guidance, and self-awareness.Noyan’s poems are notable for containing deep spiritual and philosophical elements expressed in a simple and accessible language. While emphasizing the journey of reaching divine love and closeness to Hakk (Truth, God), the poet also highlights the importance of being a virtuous individual within society. Additionally, the metaphysical connections between nature, the universe, and humanity are depicted through vivid imagery in these poems.The study further examines word choice, sentence structures, meter, and rhythm in Bedri Noyan’s poems, written under the pen names “Âşık Noyan”, “Bedri Noyan Dedebaba” and “Bedri Noyan.” As part of the traditional Turkish Sufi poetry genre, these poems, written in 6-, 7-, and 8-syllable meters, stand out with their rhythm and harmony created through rhyme, repeated words, and pauses within the lines. Out of the 23 poems studied, three were written using the aruz meter, following the pattern of Mef’ûlü mefâîlü mefâîlü fa’ûlün The poet employs simple sentences, recurring expressions, and direct addresses to effectively convey spiritual depth to the reader. In Noyan’s work, the challenges faced by the dervish in reaching divine love, the discipline of the self, and the path to divine truth are supported by a harmonious poetic structure.These unpublished poems of Bedri Noyan Dedebaba are crafted with an original style that reflects the spiritual depth and didactic nature of the Sufi tradition. Presented with simplicity, rhythm, and harmony, these poems can be regarded as significant works for conveying Bektashi teachings to future generations.
Keywords: Bedri Noyan Dedebaba; Bektashism; Sufism; poetry; grammatical structure; language